HISTORICAL MELODIES IN GALLUS HUSZÁR’S HYMNAL OF 1560 - Ágnes TÖRÖK (Studia Universitatis Babeş-Bolyai. Musica)
Gallus Huszár’s hymnal is the first Hungarian Protestant congregational hymnbook. The origin of its melodies is mainly from Europian sources: Luther’s songs, odes, Gregorian chants, other mediaeval melodies and their variations can be found in this cantional. The Hungarian melodies are represented by some special Gregorian variations but mostly with historical songs. The two historical song collections, Tinódi’s Cronica and the Hoffgreff Cantional printed in Kolozsvár, give model for some congregational songs in Huszár’s hymnal. In Gallus Huszár’s hymnal the group of he historical songs contains 10 songs, for 5 of which there are melodies, although all of the melodies are known from chant notes. Some of them were new variations or new melodies for well-known poems but one of them was a newly discovered historical melody. This new melody is András Szegedi’s historia “De expugnatione urbis Ierusolimitanae”.